Updates in the Prevalence of Rotavirus Gastroenteritis in Babylon City - Qassim Mahdi Mutlak; Manal Khalid Abdulridha; Laith M Abbas Al-Huseini (College of Pharmacy / Mustansiriyah University, 2018)
Background: Diarrhea is a main cause of morbidity and mortality in children under 5 years old. Globally it is responsible for approximately four billion cases and three million deaths annually. In developing countries, it causes two million deaths each year. The major causative organism is rotavirus which is responsible for one-third of hospitalizations with approximately 40% mortality. Objectives: To determine the prevalence and demographic characteristics of rotavirus infection in Babylon city, Iraq. Materials and Methods: Fecal samples were taken from children with age range of 6 months to 5 years complained of diarrhea during the period beginning in October 2016 till August 2017. The age, gender, residence, the type of feeding, place of the sample collection and duration of diarrhea were recorded. Specimens were analyzed by Latex test for detection of rotavirus. Results: A total of 349 children presented with diarrhea, the rotavirus antigen was detected in 169 fecal specimens from children with diarrhea (48%). More percentages of positive rotavirus specimens were seen in the 5year of age. No gender differences were observed, meanwhile samples obtained from rural areas and breastfed children showed less rotavirus positive infection. Conclusion: The present study confirms that rotavirus infection is still currently a prevalent gastroenteritis causative agent and required careful clinical attention. Pediatricians and health care providers are needed to be encouraged to take into account the children who at risk for developing rotavirus infection including age, residence and type of feeding.